Fotografias de órgãos reprodutivos de angiospermas: uma técnica para identificação de plantas por alunos do ensino médio - Silva, Erivaldo Correia da (2020)
The theme of this research work is the importance of using mobile media as a support tool in the process of teaching and learning botany for high school students. This work intends to make an analysis of how the cell phone or smartphone can be used as a didactic tool to aid in the acquisition of knowledge about plants, for this purpose, making use of the cell phone for the didactic practice of plant photography by students, seeking to awaken in them the awareness of the importance of preserving plants. This research has a qualitative and quantitative approach, of the applied type, with the participation of 30 students of the second grade, from a state public school in Paraíba. Throughout the work, the students assumed the role of protagonists, through the resolution of problems proposed and/or raised during the activities, culminating in a meaningful learning, once a list of the students previous knowledge and the new knowledge constructed with the practical reality in their lives. Finally, the students made a guide for identifying plants with the photos obtained by them during field classes and in their places of residence. The research shows that, despite being part of all aspects of the students’ lives, the plants are unnoticed, even by students who live in rural areas, because when asked about the importance of studying the plants, none of the interviewees gave answers, that the study of plants is very important, this attracted a lot of attention. The research also showed that, with the aid of the cell phone, the botanical blindness of the students who were part of it was at least mitigated, as an increase in the number of plants recognized by the students was perceived.